Profitability Ratio Analysis in Assessing Financial Performance at PT. Bank Mandiri (Persero) Tbk - Iin Musdalifah WS; Romansyah Sahabuddin; Nurman Nurman (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2024)
Measuring financial performance is important because a healthy bank will influence public trust and the achievement of an effective and efficient economic system. This research aims to determine the financial performance of PT. Bank Mandiri (Persero) Tbk in 2018-2022. The variables of this research are financial performance, return on assets, return on equity, net profit margin and operating expenses, operating income. The population and sample of this research are financial reports in the form of balance sheets and profit and loss from PT. Bank Mandiri (Persero) Tbk 2018-2022. Data collection was carried out using documentation techniques. The results of this research indicate that the financial performance of PT. Bank Mandiri (Persero) Tbk in 2018-2022 based on Bank Indonesia standards is classified as healthy. This is influenced by an increase in interest income, which causes growth in net profit.